(untitled) (Eurasian Scientific Herald, 2025)
In the context of digital economic transformation, Big Data technologies have become a crucial tool for analyzing and forecasting consumer demand. This article explores the theoretical foundations of Big Data and its application in modern demand forecasting approaches. Special attention is paid to data sources, analytical methods, and visualization techniques. The paper presents real-world cases from Amazon, Walmart, and Netflix, demonstrating the practical value of Big Data. A comparative analysis of data volume versus forecast accuracy is provided. The study highlights the strategic advantages, challenges, and future prospects of implementing Big Data technologies in demand analysis. The article concludes that Big Data is a strategic resource for enhancing supply chain efficiency, enabling personalized marketing, and supporting sustainable business growth in the digital economy